Love and Money: A Theoretical and Empirical Analysis of Household Sorting and Inequality* - Fernandez, Raquel; Guner, Nezih; Knowles, John (Quarterly Journal of Economics, 2005)
This paper examines the interactions between household formation, inequality, and per capita income. We develop a model in which agents decide to become skilled or unskilled and form households. We show that the equilibrium sorting of spouses by skill type (their correlation in skills) is an increasing function of the skill premium. In the absence of perfect capital markets, the economy can converge to different steady states, depending upon initial conditions. The degree of marital sorting and wage inequality is positively correlated across steady states and negatively correlated with per capita income. We use household surveys from 34 countries to construct several measures of the skill premium and of the degree of correlation of spouses' education (marital sorting). For all our measures, we find a positive and significant relationship between the two variables. We also find that sorting and per capita GDP are negatively correlated and that greater discrimination against women leads to more sorting, in line with the predictions of our model.